1978
DOI: 10.1111/j.1399-0039.1978.tb01281.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐H‐2Dd Antibodies Cross‐React with HLA—A11 and Aw31

Abstract: Significant correlation was found between the cytotoxicity scoring grade (CSG) of an alloimmune mouse anti--H--2Dd serum with the presence of HLA--A11 and HLA--Aw31 on human lymphocytes. The finding shows a new type of H--2/HLA cross-reactivity and a hitherto unknown relationship (XENO-CREG) between two HLA antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Strong cytotoxic reactions of most sera were correlated with the presence on the human lymphocytes of the HLA antigens A l l , Aw31, B12, B17 or B27. similar immunization procedure (Ivdnyi et al 1978b). Some sera showed the strongest cross-reactions with A1 1-and/or Aw3l-positive cells; others with B12-, B17-and/or B27-positive cells.…”
Section: Anti-h-2dd Immunization (Donor B1 Oa Recipient B1 Oa(4r))mentioning
confidence: 86%
“…Strong cytotoxic reactions of most sera were correlated with the presence on the human lymphocytes of the HLA antigens A l l , Aw31, B12, B17 or B27. similar immunization procedure (Ivdnyi et al 1978b). Some sera showed the strongest cross-reactions with A1 1-and/or Aw3l-positive cells; others with B12-, B17-and/or B27-positive cells.…”
Section: Anti-h-2dd Immunization (Donor B1 Oa Recipient B1 Oa(4r))mentioning
confidence: 86%
“…For instance, Ivanyi et al [15] reported that anti-H-2s antibodies were able to react with HLA-All and, in a system close to LFA-1, a rat anti-(mouse Mac-1) has been shown to bind human monocytes and polymorphonuclear leucocytes [3].…”
Section: Discussionmentioning
confidence: 99%